Climate change anxiety and pro-environmental behaviours: disentangling gender disparities - Pinho, Mariana (Frontiers in Sociology, 2025)
IntroductionClimate change represents the most significant environmental and social issue of our time. Climate change anxiety has been identified as a relevant consequence of climate change globally.MethodsThe current study explored how climate change anxiety and pro-environmental behaviour vary with gender and social psychological characteristics, using a nationally representative Portuguese sample.ResultsThe findings revealed that women reported higher levels of climate change anxiety compared to men, and this was driven by women’s higher levels of climate change anxiety cognitive impairment. Women also indicated more frequent pro-environmental behaviours, higher levels of environmental identity and climate change perceptions than men. The findings further showed similar relations for men and women, between social psychological mechanisms (environmental identity and climate change perceptions) and their impact on climate change anxiety and some types of pro-environmental behaviours. The results also demonstrated that climate change perceptions mediated the effect of environmental identity on pro-environmental behaviours and those mediations were further moderated by gender.DiscussionThe results highlight the importance of exploring the gender gap in environmental related attitudes and behaviours and the incorporation of gender mainstreaming in environmental sustainability policies and programmes.